Epiphytic yeasts from Piperaceae as biocontrol agents for foot rot of black pepper caused by Phytophthora capsici - dian safitri; SURYO WIYONO; BONNY POERNOMO WAHYU SOEKARNO; ACHMAD ACHMAD (Biodiversitas Journal of Biological Diversity, 2021)
Abstract. Safitri D, Wiyono S, Soekarno BPW, Achmad. 2021. Epiphytic yeasts from Piperaceae as biocontrol agents for foot rot of black pepper caused by Phytophthora capsici. Biodiversitas 22: 1895-1901. Phytophthora capsici, is a causative agent of footrot disease, is the primary pathogen in black pepper (Piper nigrum L.). Footrot disease may cause a loss of 67% black pepper production. Yeast as a biocontrol is a promising technique to control foot rot disease. This study aimed to isolate, characterize yeasts from several species of Piper and determine their effectiveness against foot rot disease. Epiphytic yeasts were isolated from roots, stems, and leaves of Piper nigrum, P. retrofractum, and P. ornatum. The epiphytic yeasts were tested for their antagonistic activity against P. capsici as biocontrol agents. The antagonistic activity was observed through antibiosis mechanisms, volatile organic compound production, hyperparasitism, and the production of ?1-1,3 glucanase enzyme. A total of 48 epiphytic yeasts were isolated from Piper species. There were five isolates with high antibiosis activity in vitro, i.e. EPT23, E62, EPT63, EPT69, EPT70, and identified through molecular identification as Rhodotorula glutinis, Cryptococcus magnus, Filobasidium globisporum, R. mucilaginosa, H. oryzae, respectively. The selected yeast showed biocontrol activity against foot rot disease ranged from 56.7 to 80.0%.